ECOLOGY IS THE FOUNDATION OF A GREEN ECONOMY - Kamilov Abdusalim Abdullayevich (Web of Journals Publishing, 2024)
This article explores the historical evolution of humanity's ecological relationship with nature, emphasizing the ethical dimensions of these interactions. It delves into the patterns and transformations of human behavior towards the environment over time, highlighting key ethical challenges and considerations. By examining historical contexts, the study provides insights into how ethical principles have shaped, and continue to shape, humanity's approach to ecological stewardship and sustainable coexistence with nature.
Keywords: Ecological ethics,